Preparation method of modified carboxymethyl cellulose lithium for lithium ion battery
By simultaneously performing decarboxylation, acidification, hydrolysis and lithiation in the preparation of carboxymethyl cellulose lithium, and using silver catalytic and graft polymerization technology, the shortcomings of the preparation method of carboxymethyl cellulose lithium in the prior art are solved, and the effects of high lithium content, high purity and enhanced adhesive properties are achieved.
Patent Information
- Application Number
- CN202510349105.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-24
AI Technical Summary
In the prior art, the preparation method of carboxymethyl cellulose lithium has problems such as low substitution rate, low purity, high cost and high risk.
Modified carboxymethylcellulose lithium containing a multi-hydrogen bond structure was prepared by simultaneously performing decarboxylation and acidification, hydrolysis and lithiation, combined with silver catalytic and graft polymerization technology.
The lithium content and purity of carboxymethylcellulose lithium is improved, its adhesive properties are enhanced, and the preparation and purification process is simplified.
Smart Images

Figure CN119842016A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical modification of natural polymer materials, and in particular relates to a method for preparing modified lithium carboxymethyl cellulose for lithium ion batteries. Background Art
[0002] Lithium carboxymethyl cellulose is a carboxymethylated derivative of cellulose, which is a water-soluble ionic cellulose ether obtained after chemical modification. Because lithium carboxymethyl cellulose has the characteristics of thickening, water retention, emulsification and dispersion in water, it is used in lithium batteries. As a new type of auxiliary material for lithium battery negative electrode adhesive, lithium carboxymethyl cellulose plays two main roles. First, as an adhesive, it tightly bonds the negative electrode active materials such as graphite, silicon carbon and other negative electrode to the collector to maintain the stability of the battery during the charge and discharge process; second, as an auxiliary lithium supplement material, it provides a lithium ion reservoir, which can improve the charge and discharge capacity and rate performance of lithium batteries.
[0003] In the prior art, the main synthesis methods of CMC-Li are: (1) direct lithiation method: directly alkalize the cellulose starting material and introduce carboxymethyl groups, then use lithium compounds to complete lithiation to avoid sodium salt intermediates, but the substitution rate of CMC-Li is low; (2) acidification-lithium salt exchange method: first convert sodium carboxymethyl cellulose (CMC-Na) into acid carboxymethyl cellulose (H-CMC), and then react with lithium salt to replace H + For Li + , generating CMC-Li, which has higher purity, but if the acidification is not complete, Na may remain + ; (3) Ion exchange method: exchange the Na in CMC-Na with cation exchange resin or solution + Replaced by Li + , high exchange efficiency, good product purity, but high cost and long time consumption. Patent CN 115636882 uses lithium diisopropylamide and butyl lithium as auxiliary reagents to activate and alkalize cellulose, and then performs etherification reaction to finally obtain lithium carboxymethyl cellulose, which overcomes the defects of insufficient contact between LiOH and cellulose and low alkalization degree during the alkalization process. However, the lithium diisopropylamide and butyl lithium used in it are highly active, and anhydrous solvents are required to react at low temperatures, which is costly and dangerous. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing modified carboxymethyl cellulose lithium for lithium ion batteries. The present invention carries out decarboxylation and acidification simultaneously, and carries out hydrolysis and lithiation simultaneously. The preparation and purification are simple. Additional carboxyl groups and hydroxyl groups are introduced after grafting and hydrolysis. The lithium content of the obtained modified carboxymethyl cellulose lithium is higher than that of ordinary carboxymethyl cellulose lithium. The grafted branched polymer contains a multi-hydrogen bond structure, and the bonding performance is enhanced.
[0005] The technical scheme for achieving the purpose of the present invention is as follows: A method for preparing modified carboxymethyl cellulose lithium for lithium ion batteries comprises the following steps: (1) Decarboxylation and acidification: In an inert gas atmosphere, disperse sodium carboxymethyl cellulose and peroxide in water, disperse silver nitrate in a solvent, mix and stir at 40-50 °C for at least 5 min; (2) Grafting: dispersing a carboxylic acid monomer, a hydroxyl monomer and silver nitrate in a solvent, mixing and adding to step (1), stirring at 50-70°C for at least 1 hour, vacuum filtering, and after filtering, washing the solid with alcohol and deionized water at least twice in sequence to obtain a grafted polymer; (3) Hydrolysis and lithiation: The grafted polymer obtained in step (2) is sequentially added with a lithium hydroxide aqueous solution and an alcohol for hydrolysis and lithiation, and stirred until the solid is dissolved, and then continued to stir to obtain a crude product of lithium carboxymethyl cellulose; (4) Purification: neutralizing, filtering, washing, drying and pulverizing the crude lithium carboxymethyl cellulose obtained in step (3) to obtain modified lithium carboxymethyl cellulose; The carboxylic acid monomer has one or more of the following molecular structures: , , and , in Formula I, R1 is one or more of methyl, ethyl or hydrogen, and n is 1 to 10; The hydroxyl monomer has one or more of the following molecular structures: , , and , in formula II, R1 is one or more of methyl, ethyl or hydrogen, m is 1 to 10, and i is 0 to 5; At least one of the carboxylic acid monomer and the hydroxyl monomer contains a maleimide structure.
[0006] Steps (1) and (2) of the present invention are silver-catalyzed decarboxylation free radical polymerization. The carboxyl groups in sodium carboxymethyl cellulose are removed to form free radicals to initiate polymerization of carboxylic acid monomers and hydroxyl monomers. In step (2), part of silver nitrate is added to remove the carboxyl groups of the carboxylic acid monomers to form free radicals, which further initiate polymerization to form branched structures, branched imide and hydroxyl structures. That is, the silver-catalyzed decarboxylation in step (1) can remove part of the carboxyl groups in sodium carboxymethyl cellulose, and the solution is an acidic solution, so that the remaining sodium carboxylate is converted into a carboxylic acid structure. The purpose of step (2) is to introduce imide, hydroxyl and a small amount of carboxyl structures. Finally, the solid structure obtained is further washed with deionized water to remove the Na + .
[0007] The present invention adjusts the branching degree of the grafted product by adjusting the silver nitrate content and ratio in step (1) and step (2).
[0008] During the polymerization of step (2), the molecular weight of the grafted polymer and the viscosity after hydrolysis are adjusted by adjusting the size of the rigid imide ring, acrylamide or acrylate structure and the above-mentioned molecular structure of formula I and formula II. The specific mechanism is as follows: (i) When the proportion of the rigid imide ring increases, as the polymerization proceeds, the molecular weight gradually increases, and the rigid structure causes its solubility in the solvent to decrease, resulting in a decrease in water solubility and product precipitation; (ii) When the proportion of acrylamide or acrylate structure increases, the rigidity of the polymer is reduced, and the solubility of the polymer requires a higher molecular weight to precipitate; (iii) When m and n of the molecular structure of formula I and formula II increase, although the flexibility of the polymer can be increased to a certain extent, when the hydrophobic structure is too large, the water solubility of the polymer will be reduced, and it will also cause it to precipitate prematurely; (iv) When i of the molecular structure of formula I and formula II increases, its structure can increase its water solubility and flexibility together, but too long a chain will lead to a decrease in viscosity. That is, the introduction of imide rings and hydrophobic structures causes the polymer to become less soluble and precipitate, and a relatively pure intermediate product can be obtained by simple treatment.
[0009] The second effect of the cyclic imide structure introduced in the present invention is that the imide ring structure is an unstable structure under alkaline conditions and can be hydrolyzed by LiOH. After hydrolysis, the five-membered ring is opened and loses its rigid structure. In addition, a large amount of lithium carboxylate structure is introduced, which greatly increases the flexibility and hydrophilicity of the polymer and has good solubility in water. The specific mechanism is as follows:
[0010] It should be noted that the amide group is very stable and will not be easily hydrolyzed by ordinary strong bases below 80°C. Hydrazine or hydroxylamine is often used to hydrolyze amides.
[0011] According to the above mechanism, the present invention controls the structure and molecular weight of the grafted polymer by the monomer structure and ratio and the silver nitrate content, thereby obtaining modified lithium carboxymethyl cellulose with different viscosities. By controlling the hydrolysis and ring opening of the cyclic imide, its water solubility is controlled, and low Na is obtained by acidification, decarboxylation, grafting and purification in steps (1) and (2). + The intermediate product with high Li content is hydrolyzed by LiOH in step (3) to obtain a water-soluble modified carboxymethyl cellulose lithium with ultra-high Li content.
[0012] Preferably, in step (1), the content of sodium carboxymethyl cellulose in the aqueous solution is 1-2 wt%, the content of peroxide in the aqueous solution is 2.0-4.0 wt%, the solvent is at least one of tetrahydrofuran and acetonitrile, and the content of silver nitrate in the solvent is 0.025-0.20 wt%.
[0013] Preferably, in step (2), the content of the carboxylic acid monomer in the solvent is 0.1-2.0 wt %, the content of the hydroxyl monomer in the solvent is 2.0-6.0 wt %, and the content of the silver nitrate in the solvent is 0.025-0.20 wt %.
[0014] Preferably, the volume ratio of the water in step (1) to the solvent in step (1) is 1:(0.2-0.8), and the volume ratio of the water in step (1) to the solvent in step (2) is 1:(0.2-0.8).
[0015] Preferably, the mass fraction of the lithium hydroxide aqueous solution in step (3) is 5-12 wt.%; the volume ratio of the alcohol to the lithium hydroxide aqueous solution is (1:1)-(1:3), the alcohol is at least one of methanol and ethanol, the temperature of the hydrolysis and lithiation reaction is 20-50°C, and the reaction time is stirring until the solid is completely dissolved and then continuing to stir for 5-60 min.
[0016] Preferably, the neutralization treatment in step (4) is to add glacial acetic acid to adjust the pH to 7-9, the washing is performed by at least one of water and ethanol; the drying is performed by at least one of vacuum drying at 60-70°C and normal pressure drying at 90-110°C; and the particle size of the modified lithium carboxymethyl cellulose obtained after the pulverization treatment is not less than 200 mesh.
[0017] Beneficial Effects
[0018] The invention has the following beneficial effects: the invention carries out decarboxylation and acidification simultaneously, carries out hydrolysis and lithiation simultaneously, utilizes the rigid structure of polymaleimide to reduce the solubility of the product and the property of easy alkaline hydrolysis, makes the preparation and purification of the polymaleimide very convenient, and the purity of the obtained product is also high; during hydrolysis, the polymaleimide ring opens and loses the rigid structure, increases the flexibility of the polymer, and forms a lithium carboxylate structure to enhance the water solubility, the lithium content of the obtained modified carboxymethyl cellulose lithium is higher than that of ordinary carboxymethyl cellulose lithium, the grafted branched polymer contains more hydrogen bond structures, the branched structure and the linear structure can form a semi-interpenetrating network structure and multi-hydrogen interaction to improve its bonding performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The schematic diagram of the synthesis and structure of the modified lithium carboxymethyl cellulose of the present invention is shown; Figure 2 This is a partial infrared spectrum of the modified lithium carboxymethyl cellulose of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0022] The raw materials and equipment used in the embodiments and comparative examples are described as follows: Sodium carboxymethyl cellulose: homemade or commercially available, MW250000 (DS=0.9), 1500-3100 mPa.s; Silver nitrate: purchased from Sinopharm Reagent; Peroxide: Potassium persulfate, purchased from Sinopharm Reagent; Ethanolamine: purchased from Maclean; Diglycolamine: purchased from Wengjiang Reagent; 1-(2-Aminoethoxy)-2-methoxyethane: purchased from Shanghai Bid Pharmaceuticals; Aminopolyethylene glycol monomethyl ether: MW: 600, purchased from Wengjiang Reagent; β-Alanine: purchased from Anaiji Chemical; Maleic anhydride: purchased from Maclean; Acryloyl chloride: purchased from Maclean; Lithium hydroxide: purchased from Maclean; Polyvinylidene fluoride (PVDF): purchased from MacLean; Carboxylic acid monomer 1: Acrylic acid, purchased from Maclean; Carboxylic acid monomer 2: Obtained by acylation of acryloyl chloride with β-alanine or commercially available; Hydroxyl monomer 1: Obtained by reaction of maleic anhydride with ethanolamine or commercially available; Hydroxyl monomer 2: Obtained by reacting maleic anhydride with diglycolamine or commercially available; Hydroxyl monomer 3: Obtained by reacting maleic anhydride with aminopolyethylene glycol monomethyl ether or commercially available; Hydroxyl monomer 4: It is obtained by acylation of acryloyl chloride with ethanolamine or commercially available.
[0023] The following is the test method of the performance parameters involved in the present invention: Determination of molecular weight and polydispersity index (PDI) by gel permeation chromatography: The molecular weight was detected by GPC method on high performance liquid chromatography (HPLC) (Agilent HPLC 1260 InfinityII, Agilent PL aquagel-OH 508um column). The Agilent 1260 Infinity II liquid chromatography system has the hardware foundation of gel permeation chromatography (GPC), which can support multi-column switching and use gel chromatography columns to test the number average molecular weight.
[0024] Viscosity measurement: Weigh 5.0 g each of the modified lithium carboxymethyl cellulose, sodium carboxymethyl cellulose and PVDF in the examples and comparative examples that have been dried at 105°C for 2 h, accurate to 0.001 g for standby use, take a number of wide-mouth bottles, measure 495 ml of water into each wide-mouth bottle, place each wide-mouth bottle on a heating jacket, adjust the speed to 200-400 r / min, add each sample into a different wide-mouth bottle, slowly adjust the stirring speed to 900 r / min, stir for about 2 h, until the sample is completely dissolved and evenly dissolved, and use a DV2T viscometer to conduct the test.
[0025] Peel test: The evaluation of adhesion performance is usually carried out through a peel strength test. When performing the peel strength test, the pre-prepared electrode sheet is first pasted on the aluminum plate substrate, and then firmly adhered to the electrode-coated surface with 3M tape. The specific operation is to stick a 120×25 mm electrode sample on 3M transparent tape, stick it on the coating and pull it at a 180° angle. The force required to pull the tape at a fixed speed of 100 mm / min was recorded; the preparation method of the electrode sheet is as follows: graphite: acetylene black: SBR: modified carboxymethyl cellulose lithium (or other binder) with a mass ratio of 95:1.5:1.5:2 are weighed respectively, and the modified carboxymethyl cellulose lithium (binder) is dissolved by a solvent, and the solvent is appropriately added according to the viscosity of the solution, and the weighed graphite and acetylene black are added to an agate mortar for grinding, and the dissolved modified carboxymethyl cellulose lithium (or other binder) is added after mixing evenly, and an appropriate amount of solvent is added again according to the viscosity of the slurry, and a small beaker is sealed with plastic wrap, and placed on a stirrer for stirring for 12 h, and the stirred electrode slurry is coated on a copper foil wiped and dried with anhydrous ethanol to obtain an electrode sheet. The electrode sheet is placed in a 50 ℃ oven and dried for 12 h to obtain an electrode sheet.
[0026] Example 1
[0027] A method for preparing modified lithium carboxymethyl cellulose for lithium ion batteries comprises the following steps: (1) Decarboxylation and acidification: In an inert gas atmosphere, disperse 20 g of sodium carboxymethyl cellulose and 40 g of peroxide in 1000 ml of water, disperse 0.4 g of silver nitrate in 500 ml of tetrahydrofuran, mix and stir at 50 °C for 10 min; (2) Grafting: Disperse 5 g of carboxylic acid monomer 1, 25 g of hydroxyl monomer 1 and 0.2 g of silver nitrate in 500 ml of tetrahydrofuran, mix and add to step (1), stir at 65 °C for 3 h, vacuum filter, wash the solid twice with alcohol and deionized water in sequence, and filter to obtain a grafted polymer; (3) Hydrolysis and lithiation: The grafted polymer obtained in step (2) is sequentially added with a 12 wt.% lithium hydroxide aqueous solution and methanol, with the volume ratio of the lithium hydroxide aqueous solution to the methanol being 1:1, and hydrolyzed and lithiation is performed at 35°C. After stirring until the solid is dissolved, stirring is continued for 20 minutes to obtain a crude lithium carboxymethyl cellulose; (4) Purification: The crude lithium carboxymethyl cellulose obtained in step (3) was added with glacial acetic acid to adjust the pH to 8. The solid obtained after filtration was washed three times with water and ethanol in sequence, dried at 90°C under normal pressure, and crushed to a size of not less than 200 meshes to obtain modified lithium carboxymethyl cellulose 1.
[0028] Example 2
[0029] Compared with the preparation method of Example 1, the difference is that the 0.2 g of silver nitrate in step (2) is replaced by 0.4 g.
[0030] Example 3
[0031] Compared with the preparation method of Example 1, the difference is that 5 g of carboxylic acid monomer 1 and 25 g of hydroxyl monomer 1 in step (2) are replaced by 10 g of carboxylic acid monomer 1 and 20 g of hydroxyl monomer 1.
[0032] Example 4
[0033] Compared with the preparation method of Example 1, the difference is that 5 g of carboxylic acid monomer 1 in step (2) is replaced by 5 g of carboxylic acid monomer 2.
[0034] Example 5
[0035] Compared with the preparation method of Example 1, the difference is that 25 g of hydroxyl monomer 1 in step (2) is replaced by 25 g of hydroxyl monomer 2.
[0036] Comparative Example 1 Compared with the preparation method of Example 1, the difference is that 25 g of hydroxyl monomer 1 in step (2) is replaced by 25 g of hydroxyl monomer 3. During the preparation, the solid in step (2) cannot be precipitated, and it is necessary to remove the solvent and then purify it by a graded precipitation method, which is more complicated.
[0037] Comparative Example 2 Compared with the preparation method of Example 1, the difference is that 25 g of hydroxyl monomer 1 in step (2) is replaced by 25 g of hydroxyl monomer 4.
[0038] Comparative Example 3 Sodium carboxymethyl cellulose is used.
[0039] Comparative Example 4 Using PVDF.
[0040] Molecular weight test example: In an inert gas atmosphere, carboxylic acid monomer 2 and peroxide are dispersed in water, carboxylic acid monomer, hydroxyl monomer and silver nitrate solution are added after mixing, carboxylic acid monomer 2 is used to replace sodium carboxymethyl cellulose, and the free radical formed after decarboxylation is used as an initiator. The carboxylic acid monomer and hydroxyl monomer added subsequently are monomers, and the molar ratio of the initiator to the monomer is 1:30. The structures or proportions of the carboxylic acid monomer, hydroxyl monomer, peroxide and silver nitrate are polymerized according to Examples 1 to 5 and Comparative Examples 1 to 2, respectively, and the molecular weight and degree of branching are measured.
[0041] Table 1 Molecular weight test of corresponding ratios of examples and comparative examples
[0042] The data in Table 1 are the properties of branched polymers initiated by small molecules, and the properties of modified lithium carboxymethyl cellulose can be inferred from them. It can be seen from the data in Table 1 that the molecular weights of Examples 1 and 2 are similar, but the PDI of Example 2 is larger. In the proportion of Example 2, the content of silver nitrate catalyst in step (2) is increased, resulting in an increase in the degree of branching; the PDI of Example 3 is slightly larger than that of Example 1, and the molecular weight is also larger. Compared with Example 1, the proportion of carboxyl monomer 1 in Example 3 is increased, because carboxyl monomer 1 does not contain a rigid ring structure, while hydroxyl monomer 1 is a ring structure, and the solubility of the solid polymer is better than that of Example 1, so its molecular weight is larger; compared with Example 1, the molecular weight and PDI of Example 4 are slightly increased, which is because the structure of carboxylic acid monomer 2 is less hindered by the carboxyl group in carboxylic acid monomer 1 and is easier to be initiated; compared with Example 1, the molecular weight of Example 5 is slightly increased, which is because the flexible group introduced by hydroxyl monomer 2 is longer. Comparative Example 1 introduces a long hydroxyl monomer, so the solubility is better and the molecular weight is greatly increased; the molecular weight of Comparative Example 2 is increased more because no rigid monomer is used.
[0043] Table 2 Performance test of examples and comparative examples
[0044] As can be seen from Table 2, the effect of Example 2 is better than that of Example 1, which is because the degree of branching of Example 2 is higher and the interaction of hydrogen bonds is more obvious; the performance of Example 3 is better than that of Example 1, and the molecular weight of Example 3 is larger, indicating that the degree of polymerization is higher and the hydrogen bonds are slightly more than that of Example 1, so its hydrogen bonds and intermolecular forces are better than those of Example 1; the viscosity and peel strength of Example 4 are the largest. Compared with other examples, 5 g of carboxylic acid monomer 1 used in Example 4 is replaced by 5 g of carboxylic acid monomer 2. As can be seen from Table 1, the polymer grafted on the surface of Example 4 has a larger degree of branching. In addition, carboxylic acid monomer 2 contains NH bonds, which further enhances the interaction of intermolecular hydrogen bonds; the performance of Example 5 is also better than that of Example 1, and the mechanism is the same as that of Example 3; Comparative Example 1 is synthesized using hydroxyl monomer 3, which is obtained by maleic anhydride and aminopolyethylene glycol monomethyl ether. Compared with Examples 1 and 5, it has a larger steric hindrance and does not contain hydroxyl groups at the end, which reduces the interaction between celluloses, thereby reducing the viscosity. Comparative Example 2 does not use a rigid structure, and its molecular weight is relatively large, but because there is no imide group, it cannot be hydrolyzed to obtain a lithium carboxylate structure, so the hydrogen bond interaction is greatly reduced, and the molecular structure has good water solubility and is difficult to purify. Comparative Examples 3 and 4 are comparative tests of sodium carboxymethyl cellulose and polyvinylidene fluoride, and their performance is not as good as the modified lithium carboxymethyl cellulose prepared in the embodiment of the present invention.
[0045] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing modified carboxymethyl cellulose lithium for lithium ion batteries, characterized in that: The following steps are involved: (1) Decarboxylation and acidification: In an inert gas atmosphere, disperse sodium carboxymethyl cellulose and peroxide in water, disperse silver nitrate in a solvent, mix and stir at 40-50 °C for at least 5 min; (2) Grafting: disperse the carboxylic acid monomer, hydroxyl monomer and silver nitrate in a solvent, mix and add to the mixture of step (1), heat to 50-70°C and stir for at least 1 hour, vacuum filter, wash with alcohol and deionized water at least twice in sequence, filter to obtain a grafted polymer; (3) Hydrolysis and lithiation: The grafted polymer obtained in step (2) is sequentially added with a lithium hydroxide aqueous solution and an alcohol for hydrolysis and lithiation, and stirred until the solid is dissolved, and then continued to stir to obtain a crude product of lithium carboxymethyl cellulose; (4) Purification: neutralizing, washing, drying and pulverizing the crude lithium carboxymethyl cellulose obtained in step (3) to obtain modified lithium carboxymethyl cellulose; The carboxylic acid monomer has one or more of the following molecular structures: , , and , in Formula I, R1 is one or more of methyl, ethyl or hydrogen, and n is 1 to 10; The hydroxyl monomer has one or more of the following molecular structures: , , and , in formula II, R1 is one or more of methyl, ethyl or hydrogen, m is 1 to 10, and i is 0 to 5; At least one of the carboxylic acid monomer and the hydroxyl monomer contains a maleimide structure.
2. The method for preparing modified carboxymethyl cellulose lithium for lithium ion batteries according to claim 1, characterized in that: In step (1), the content of sodium carboxymethyl cellulose in the aqueous solution is 1-2 wt %, the content of peroxide in the aqueous solution is 2.0-4.0 wt %, the solvent is at least one of tetrahydrofuran and acetonitrile, and the content of silver nitrate in the solvent is 0.025-0.20 wt %.
3. The method for preparing modified carboxymethyl cellulose lithium for lithium ion batteries according to claim 1, characterized in that: In step (2), the content of the carboxylic acid monomer in the solvent is 0.1-2.0 wt %, the content of the hydroxyl monomer in the solvent is 2.0-6.0 wt %, and the content of the silver nitrate in the solvent is 0.025-0.20 wt %.
4. The method for preparing modified carboxymethyl cellulose lithium for lithium ion batteries according to claim 1, characterized in that: The volume ratio of the water in step (1) to the solvent in step (1) is 1:(0.2-0.8), and the volume ratio of the water in step (1) to the solvent in step (2) is 1:(0.2-0.8).
5. The method for preparing modified carboxymethyl cellulose lithium for lithium ion batteries according to claim 1, characterized in that: In step (3), the mass fraction of the lithium hydroxide aqueous solution is 5-12 wt.%; the volume ratio of the alcohol to the lithium hydroxide aqueous solution is (1:1)-(1:3), the alcohol is at least one of methanol and ethanol, the temperature of the hydrolysis and lithiation reaction is 20-50°C, and the reaction time is stirring until the solid is completely dissolved and then continuing to stir for 5-60 min.
6. The method for preparing modified carboxymethyl cellulose lithium for lithium ion batteries according to claim 1, characterized in that: The neutralization treatment in step (4) is to add glacial acetic acid to adjust the pH to 7-9, the washing is performed by at least one of water and ethanol; the drying is performed by at least one of vacuum drying at 60-70°C and normal pressure drying at 90-110°C; the particle size of the modified lithium carboxymethyl cellulose obtained after the pulverization treatment is not less than 200 mesh.
Citation Information
Patent Citations
Preparation method of low sodium salt carboxymethyl cellulose lithium
CN106366203A
Preparation method of nano CMCLi
CN109503723A
Production process of self-esterification reaction sodium carboxymethyl cellulose
CN112707969A
Lithium carboxymethyl cellulose as well as preparation method and application thereof
CN115246889A
Modification and preparation method of lithium battery grade carboxymethyl cellulose lithium material
CN116535527A
Cited By
Lithium battery adhesive and preparation method thereof
CN120424606A
Lithium battery adhesive and preparation method thereof
CN120424606B